Pediatric End-of-Life: Comment on the Document of the Pediatric Clinical Ethics Committee of the Padua University Hospital (BioLaw Journal - Rivista di BioDiritto, 2026)
The article addresses the main ethical issues that may arise in a pediatric setting and explores how a Pediatric Clinical Ethics Committee (CEC) can promote patient-centered care for minors. It analyses the document End of Life: Ethical Considerations from the Pediatric Context, which was approved in 2023 by the Pediatric CEC of the Azienda Ospedale-Università Padova. As well as raising awareness of end-of-life care in relation to developmental age, the document outlines the role of a pediatric CEC when faced with a request for Physician-Assisted Suicide from a hospitalized pediatric patient or one under pediatric care. Finally, the contribution of pediatric palliative care in providing comprehensive care for the minor and his family is emphasized.
Keywords: pediatric end-of-life; clinical ethics committee; physician-assisted suicide; lexicon on end-of-life; pediatric palliative care